IMPROVING STUDENTS’ ABILITY TO UNDERSTAND COMPARISON DEGREE BY USING STICK PUPPET - Maqfirotika, Laila; Wahono, Suparwoto Sapto; Syahbana, Rizkia Ruwanda; Putri, Rahma Aulia; Azizah, Rovinia Za’imatul (International Journal of Research on English Teaching and Applied Linguistics, 2023)
Learning grammar, particularly understanding tenses, poses challenges for students, often leading to boredom during lessons. To address this, researchers propose integrating new media, such as stick puppets, into grammar instruction to enhance student engagement. The aim is to cultivate enthusiasm, involvement, and a deeper understanding of English grammar. This study was conducted as Classroom Action Research (CAR) with tenth grade students of SMKN 3 Jember. It explored the efficacy of stick puppets as an alternative method to improve Grammar Comprehension. This research was spanning one cycle with three implementation meetings and a post-test. It utilized various data collection techniques was included; grammar scores, teacher observations, interviews, student questionnaires, and classroom observation sheets. From the implementation of stick puppets, the findings revealed notable improvement in the Grammar Comprehension of tenth-grade students at SMKN 3 Jember with a 95.65% success rate. The students demonstrated increased proficiency across vocabulary, pronunciation, grammar usage, and content which indicated that stick puppets not only enhanced comprehension but also fostered active participation and student interest.